Case reportSolid facial oedema of acne: a case report - Pastuszka, Marta; Kaszuba, Aleksandra; Kaszuba, Andrzej (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2011)
Solid facial oedema is a rarely described skin condition, which occurs as a complication of acne vulgaris. Its aetiopathogenesis has not yet been definitively clarified. However, it seems that the key role is played by chronic inflammation that can cause obstruction of lymphatic vessels, cellulitis, fibrosis and oedema. Inherited factors should also be kept in mind. In the course of the illness, painless swelling of the forehead, upper eyelids, nasolabial folds and nasal saddle is observed. In the treatment the best results are obtained with isotretinoin alone (at a dose of 0.1-0.3 mg/kg) or in a combination with an antagonist of histamine type 1 receptors – ketotifen (1 mg 2 times a day). Presentation of a 26-year-old male patient with solid facial oedema of acne, in whom complete remission was obtained after oral isotretinoin and ketotifen. The patient was admitted to the hospital because of (persistent for about 1 year) erythema and oedema of the forehead, upper eyelids and nasal saddle. Prior treatment (antibiotics, corticosteroids, calcineurin inhibitors) did not achieve clinical improvement. Detailed anamnesis revealed that the patient had been previously treated for acne vulgaris (of moderate intensity), using topical preparations with benzoyl peroxide and antibiotics and oral antibiotics (lymecycline). This treatment was completed about 6 months before the appearance of swelling. The patient was administered oral isotretinoin and ketotifen, giving complete clinical remission. Based on earlier reports and the course of therapy in the presented patient, it can be concluded that oral isotretinoin in a combination with antagonist of histamine type 1 receptors is effective in treatment of patients with this disease.